The role and efficacy of multidisciplinary council in the bone and soft tissue tumor patients - Coşkun, Sina; Dabak, Nevzat; Göçer, Hasan; Say, Ferhat (The European Research Journal, 2021)
Objectives: Bone and soft tissue tumors have become more common and recognized diseases with developing medical technologies. The life span of the patients has been prolonged with more effective treatment methods and developing technology. Regardless of their area of expertise, the concept of multidisciplinary tumor approach has emerged in recent years, since it is difficult for a single physician to manage a malignant mass treatment process. For this purpose, we aimed to share our multidisciplinary bone and soft tissue tumor council data results. Methods: Patients who were evaluated at the Department of Orthopedics and Traumatology of Ondokuz Mayis University between January 2004 and June 2017 were evaluated retrospectively. For this study, the weekly archived tumor council forms were evaluated and the data were transferred to the computer via Microsoft Excel and SPSS programs. The database for the specified years was created and the results were evaluated and the database was evaluated. Results: A total of 2788 patients were included in the study. After the patients with data deficiency were removed, 2397 patients were the subject of the study. In the evaluation of the first 1960 patients, 658 primary bone tumors, 577 primary soft tissue tumors, 356 cases of metastases and 374 non-tumoral cases were detected. The most common benign bone tumor was enchondroma, while the most common malignant bone tumor was osteosarcoma. The most common benign soft tissue tumor was lipoma, whereas the most common malignant soft tissue tumor was malignant mesenchymal tumor. The most common non-tumor cause was chronic infection. The diagnosis of 203 patients was different from the definitive diagnosis. Conclusions: In this study, we determined the epidemiological distribution of the cases evaluated in the multidisciplinary tumor council in the Middle Black Sea and the role of multidisciplinaryapproach in treatment and survival has a positive effect especially in selected patient groups.